2016
DOI: 10.1371/journal.pone.0147931
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Influenza Vaccination of Hospitalized Elderly Patients in Spain

Abstract: Vaccination of the elderly is an important factor in limiting the impact of influenza in the community. The aim of this study was to investigate the factors associated with influenza vaccination coverage in hospitalized patients aged ≥65 years hospitalized due to causes unrelated to influenza in Spain. We carried out a cross-sectional study. Bivariate analysis was performed comparing vaccinated and unvaccinated patients, taking in to account sociodemographic variables and medical risk conditions. Multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 34 publications
(66 reference statements)
7
29
0
Order By: Relevance
“…This reflects the stability of influenza vaccination attitudes and behaviours of individuals and therefore the difficulties in modifying vaccine acceptance in those who are reluctant. Consistent with findings based on self-reported vaccination or intention, we found that perception of benefits, barriers and cues to action were associated with the willingness to be vaccinated in the subsequent season this is consistent with previous results showing that a major reason to be vaccinated was the experience of getting very sick from influenza [23][24][25]. This result is not specific to influenza and was also found for instance in the context of pneumococcal vaccine, where a history of pneumonia was an independent factor associated with the willingness to receive a subsequent pneumococcal vaccine [26].…”
Section: This Higher Rate Of Influenza Vaccination Willingness Is Consupporting
confidence: 92%
“…This reflects the stability of influenza vaccination attitudes and behaviours of individuals and therefore the difficulties in modifying vaccine acceptance in those who are reluctant. Consistent with findings based on self-reported vaccination or intention, we found that perception of benefits, barriers and cues to action were associated with the willingness to be vaccinated in the subsequent season this is consistent with previous results showing that a major reason to be vaccinated was the experience of getting very sick from influenza [23][24][25]. This result is not specific to influenza and was also found for instance in the context of pneumococcal vaccine, where a history of pneumonia was an independent factor associated with the willingness to receive a subsequent pneumococcal vaccine [26].…”
Section: This Higher Rate Of Influenza Vaccination Willingness Is Consupporting
confidence: 92%
“…Methods used to evaluate vaccination uptake in the cross-sectional and cohort studies and in the systematic reviews were: questionnaires and surveys [13-15, 19, 21, 22, 25, 28, 34-36]; telephone interviews [20,23,27,29,30,33,39,41]; data retrieved from national/regional authorities and health care institutions [12,38,40,49,50]; data retrieved from medical records or vaccination registries [9,10,31,37]; combined methods [11,17,18,24]; focus group discussions [26,32]; face-to-face interviews [42]; database search [47,48].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of participants older than 65 years of study samples ranges from 11% to 100% of all initially included study participants (n= 19.604.711) from across the globe in countries from four continents and in following care settings: Community-dwelling or non-institutionalized citizens [9, 15, 21, 23, 27-31, 33, 36, 39, 42, 48, 50], nursing homes [12,38], combined settings [32,37], outpatient clinics [44], hospitals [18,22], primary care centres/clinics or practices [24,26,43,45], home-based primary care settings [10] and data bases such as the Medicare registry, national vaccine industry or settings of health services/insurance authorities [13,40,46]. In 12 studies, details about the care setting of the participants were not indicated [11,14,16,17,19,20,25,34,35,41,47,49].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations for the elderly are not only based on the inevitably growing number of co-morbidities in this age group, but also on immune-senescence. [62][63][64] Unfortunately, the effectiveness of influenza vaccines is often impaired in individuals who could benefit most from vaccination: immune-compromised and elderly individuals, as well as patients in the other high-risk groups mentioned in virtually all recommendations. Limited data are available about the added value of recently introduced adjuvanted, high-dose (HD) and quadrivalent vaccines (for review see Reperant et al 65 ).…”
Section: Vaccination Of Travellers Belonging To High-risk Groupsmentioning
confidence: 99%